Referral for Kidney Transplantation and Indicators of Quality of Dialysis Care: A Cross-sectional Study - Plantinga, Laura C. (Am J Kidney Dis, 2016)
BACKGROUND: Dialysis facility performance measures to improve access to kidney transplantation are being considered. Referral of patients for kidney transplant evaluation by the dialysis facility is one potential indicator, but limited data exist to evaluate whether referral is associated with existing dialysis facility quality indicators. STUDY DESIGN: Cross-sectional study. SETTING & PARTICIPANTS: A total of 12,926 incident (7/05–9/11) adult (aged 18-69 years) patients treated at 241 dialysis facilities with complete quality indicator information, from US national registry data linked to transplant referral data from all three Georgia kidney transplant centers. FACTORS: Facility performance on dialysis quality indicators (high, intermediate, and low tertiles). OUTCOME: Percentages of patients referred within 1 year of dialysis initiation at dialysis facility. RESULTS: Overall, a median of 25.4% of patients were referred for kidney transplantation within 1 year of dialysis initiation. Higher facility-level referral was associated with better performance with respect to standardized transplantation ratio (high, 28.6%; intermediate, 25.1%; low, 22.9%; P=0.001) and percentage waitlisted (high, 30.7%; intermediate, 26.8%; low, 19.2%; P<0.001). Facility-level referral was not associated with indicators of quality of care associated with dialysis initiation, including percentage of incident patients being informed of transplant options. For most non–transplant-related indicators of high-quality care, including those capturing mortality, morbidity, and anemia management, better performance was not associated with higher facility-level transplant referral. LIMITATIONS: Potential ecologic fallacy and residual confounding. CONCLUSIONS: Transplant referral among patients at dialysis facilities does not appear to be associated with overall quality of dialysis care at the facility. Quality indicators related to kidney transplantation were positively associated with, but not entirely correspondent with, higher percentages of patients referred for kidney transplant evaluation from dialysis facilities. These results suggest that facility-level referral, which is within the control of the dialysis facility, may provide information about the quality of dialysis care beyond current indicators.